Gastrointestinal parasites of the Saimaa ringed seal (Pusa hispida saimensis) - Hongisto, Hanna (Turun ammattikorkeakoulu, 2014)
The aim of this study was to examine the distribution of parasites in the intestinal tract of the Saimaa ringed seal (Pusa hispida saimensis). The material used in this study was collected from seal individuals which were found dead in Lake Saimaa between years 2004–2012. The age of the individuals varied from zero to five years, of which six were pups less than one year old. The examinations were performed in the facilities at the University of Eastern Finland in Joensuu in May 2014. The intestines were separated from the stomach, and the stomach was weighed. The different parts of the intestinal tracts were then separated from each other. The large and small intestines were measured; the large intestine was cut into two, and the small intestine into ten, equally long pieces. After this procedure, the intestines were opened using blunt-ended scissors and the insides were examined. Parasites were collected with a pair of tweezers and preserved in 99.5% ethanol, each placed into a Sarstedt tube labelled according to the specimen and the part of the tract where it was recovered from. The otholites were placed on a petri dish that was labelled according to the specimen and whether the samples were from stomach or intestines. All in all nine seal intestines were examined, and the total amount of parasites gathered was 1,429. Although the sampling of this work remained rather small, the results support the previous findings in many ways. Out of the nine examined samples, parasites were found from six of them. There were no parasites in three of the youngest pups. The parasites found were exclusively gastrointestinal worms known as Corynosoma magdaleni. This study shows that these worms are clearly adapted to living in the middle section of the small intestine. No worms were found from the large intestine, cecum, or from the first section of the small intestine. Saimaa ringed seal is a critically endangered species. In view of conservation, every study performed on this seal species is extremely important. The study of the seal parasites helps determine the general state of health of this animal, and plan further the protection of the species. Tämän tutkimuksen tarkoituksena oli kartoittaa saimaannorpan (Pusa hispida saimensis) suolistoloisten levinneisyyttä suoliston eri osissa. Tutkimuksessa käytetty materiaali oli kerätty Saimaan vesistöstä kuolleina löydetyistä norppayksilöistä vuosina 2004¬–2012. Yksilöiden ikä vaihteli välillä 0–5 vuotta. Kuusi yhdeksästä yksilöstä olivat alle vuoden ikäisiä poikasia. Suolten avaukset tehtiin Itä-Suomen yliopiston tiloissa Joensuussa vuoden 2014 toukokuussa. Suolet leikattiin erilleen mahasta, ja maha punnittiin. Suolen eri osat leikattiin toisistaan erilleen. Paksusuoli ja ohutsuoli mitattiin, minkä jälkeen paksusuoli leikattiin kahteen ja ohutsuoli kymmeneen yhtä suureen osaan. Tämän jälkeen suolet avattiin suolisaksilla ja sisäosat käytiin silmämääräisesti läpi. Loiset kerättiin suolen seinämästä pinseteillä ja säilöttiin 99,5-prosenttista etanolia sisältäviin Sarstedt-putkiin sen mukaan, mistä yksilöstä ja suolen osasta näyte oli kerätty. Otoliitit sekä muut kalan osat asetettiin merkatulle petrimaljalle kuivumaan. Kaiken kaikkiaan yhdeksän norppayksilön suolet avattiin, joista loisia kerättiin yhteensä 1 429 kappaletta. Tämän työn otoskoko jäi pieneksi, mutta tulokset tukevat aikaisempia tutkimuksia monin tavoin. Yhdeksästä avatusta suolesta yhteensä kuudesta löytyi loisia. Kolmesta nuorimmasta poikasesta ei löytynyt loisia. Löydetyt loiset olivat yksinomaan Corynosoma magdaleni -väkäkärsämatoja. Madot ovat selvästi erikoistuneet elämään ohutsuolen keskivaiheilla, avauksissa ei yhdestäkään näytteestä löytynyt loisia paksu- ja umpisuolesta eikä ohutsuolen alkupäästä. Saimaannorppa on erittäin uhanalainen laji. Tätä näkemystä vasten on jokainen norpalle tehty tutkimus tärkeä luonnonsuojelun näkökulmasta. Norpan loisten kartoitus auttaa selvittämään tämän nisäkäsalalajin terveydellistä tilaa, jonka pohjalta voidaan laatia suunnitelmia lajin suojelun edistämiseksi.